VOICES: An efficacious trauma-informed, gender-responsive cannabis use intervention for justice and school-referred girls with lifetime substance use history. (1st November 2021) - Tolou-Shams, Marina; Dauria, Emily F.; Folk, Johanna; Shumway, Martha; Marshall, Brandon D.L.; Rizzo, Christie J.; Messina, Nena; Covington, Stephanie; Haack, Lauren M.; Chaffee, Tonya; Brown, Larry K
Highlights: Gender and trauma-responsive intervention reduces adolescent girls' cannabis use. Sustained reduced cannabis use in justice-involved girls may prevent future legal involvement. Need for greater reach and accessibility of gender-responsive adolescent cannabis interventions. Abstract: Background: Girls have unique developmental pathways to substance use and justice system involvement, warranting gender-responsive intervention. We tested the efficacy of VOICES (a 12-session, weekly trauma-informed, gender-responsive substance use intervention) in reducing substance use and HIV/STI risk behaviors among justice- and school-referred girls. Methods: Participants were 113 girls ( M age = 15.7 years, SD = 1.4; 12 % White, 19 % Black, 15 % multi-racial; 42 % Latinx) with a history of substance use referred from juvenile justice (29 %) and school systems (71 %). Study assessments were completed at baseline, 3-, 6- and 9-months follow-up. Primary outcomes included substance use and HIV/STI risk behaviors; secondary outcomes included psychiatric symptoms (including posttraumatic stress) and delinquent acts. We hypothesized that girls randomized to the VOICES ( n = 51) versus GirlHealth (attention control; n = 62) condition would report reduced alcohol, cannabis and other substance use, HIV/STI risk behaviors, psychiatric symptoms, and delinquent acts. Results: Girls randomized to VOICES reported significantly less cannabis use over 9-month follow-up relative to the control condition (time by intervention, p < .01), but there were no between group differences over time in HIV/STI risk behavior. Girls in both conditions reported fewer psychiatric symptoms and delinquent acts over time. Conclusions: Data support the use of a trauma-informed, gender-responsive intervention to reduce cannabis use among girls with a substance use history and legal involvement; reducing cannabis use in this population has implications for preventing future justice involvement and improving public health outcomes for girls and young women, who are at disproportionate health and legal risk relative to their male counterparts.